Factors affecting activation and utilization of carbon dioxide in cyclic carbonates synthesis over Cu and Mn peraza macrocyclic complexes - Srivastava, R.; Bennur, T. H.; Srinivas, D. (Journal of Molecular Catalysis A - Chemical, 2005)
The catalytic activities of several Cu and Mn aza complexes for cyclic carbonate synthesis from CO2 and epoxides are reported. The various factors affecting activation of CO2 by metal complexes and its utilization in cyclic carbonate synthesis have been investigated. Fr-IR, UV-vis and EPR spectroscopic investigations reveal that CO2 coordinates to Cu in eta(1)-C mode of coordination. Nature of the ligand and substitution influence the lability of metal-CO2 bonding. The differences in the catalytic activities are correlated with the mode and strength of CO2 binding. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: benign synthesis; Carbon dioxide; catalysis by Cu and Mn complexes; CO2 activation; CO2 fixation; CO2 utilization; cyclic carbonates; polycarbonates; spectroscopy

Nature of manganese species in Ce1-xMnxO2-delta solid solutions synthesized by the solution combustion route - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, V. (Chemistry of Materials, 2005)
A series of manganese-cerium oxide composites with Mn concentrations in the range of 1-20 mol % in ceria was prepared by the solution combustion technique using urea as fuel. The nature, type, and oxidation state of Mn species in ceria were investigated by X-ray diffraction (XRD), diffuse reflectance UV-visible spectroscopy, electron paramagnetic resonance (EPR), X-ray photoelectron spectroscopy, and temperature-programmed reduction techniques. The study reveals that the method of preparation significantly influences the type of manganese species in ceria. Wet-impregnation, coprecipitation, and solid-state synthesis techniques lead to clustered MnOx-like species in the ceria matrix, while the present method of preparation (solution combustion route) yields a highly dispersed form of Mn species. In the reported series of samples, Mn is present mainly in +2 and +3 oxidation states and there is no evidence for the presence of Mn 41 species. Powder X-ray diffraction studies at variable temperatures (298-1323 K) indicate the formation of Ce1-xMnxO2-delta Solid solutions. No separate MnOx-type phase was detected even at 1323 K. EPR studies reveal that the isolated Mn2+ and Mn2+ species are present in at least three different structural locations: species A, Mn ions in ceria-lattice defect sites; species B, Mn ions in framework Ce4+ locations; and species C, Mn ions in interstitial locations and at the surface of ceria. The Mn3+ ions in ceria exhibit a facile reduction and reoxidation behavior when exposed to dry hydrogen and subsequently to air at elevated. temperatures. A highly dispersed state of Mn3+ and Mn2+ in ceria, facile redox behavior, and a synergistic Mn-ceria interaction are some of the unique properties of this material prepared by the solution combustion procedure.

Chemo-, regio- and stereo-selective aerial oxidation of limonene to the endo-1,2-epoxide over Mn(Salen)-sulfonated SBA-15 - Saikia, Lakshi; Srinivas, D.; Ratnasamy, Paul (Applied Catalysis A-General, 2006)
Mn(Salen) complexes immobilized on sulfonic acid-functionalized SBA-15 molecular sieves (SBA-15-pr-SO3-Mn(Salen)) catalyze the Mukaiyama-type oxidation of R-(+)-limonene selectively to the 1,2-epoxide with molecular oxygen at 298 K (Salen = N,N-ethylenebis(salicylidenaminato)). The endo-diastereomer is formed with a diasteromeric excess of 39.8%. This catalyst exhibited higher catalytic activity than ``neat'' Mn(Salen) complexes directly supported on SBA-15 or zeolite-Y. A change in the oxidation state of Mn from +3 in the ``neat'' complex to +2 when immobilized on the sulfonated surface is a probable cause for the observed enhancement of catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: aerial oxidation of limonene; catalysis by Mn(Salen) complexes; chemo-; immobilized Mn Schiff base complexes; Mesoporous molecular sieves; Mukaiyama-type oxidation; regio- and stereo-selective epoxidation; sulfonic acid-functionalized SBA-15

Fe-Zn double-metal cyanide complexes as novel, solid transesteritication catalysts - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Journal of Catalysis, 2006)
Fe-Zn double-metal cyanide complexes are currently used as catalysts for the ring-opening polymerization of epoxides, as well as the coupling of epoxides and CO2 for the production of polycarbonates. We report their novel application as highly efficient solid catalysts for the transesterification reactions of carbonates. The catalysts were prepared from aqueous solutions of ZnCl2 and K4Fe(CN)(6) in the presence of tert-butanol (complexing agent) and tri-block copolymer EO20PO70EO20 (average molecular weight, 5800; co-complexing agent). They were characterized by chemical analysis, XRD, thermal analysis, N-2 adsorption, magnetic susceptibility, SEM, and FTIR, diffuse reflectance UV-visible, EPR, and X-ray photoelectron spectroscopies. Their acidity was determined from the IR spectra of adsorbed pyridine and the temperature-programmed desorption of NH3. Catalyst samples prepared with both complexing and co-complexing agents were found to be more acidic and catalytically active than those prepared without these agents. These catalysts are more active/selective than other solid catalysts hitherto reported. Dimethyl carbonate, for example, could be synthesized with 100% selectivity and an isolated yield of >86% by the reaction of propene carbonate with methanol. The catalysts can be recycled without significant loss in activity. Lewis acidic Zn ions are the possible active sites for the transesterification reaction. (c) 2006 Published by Elsevier Inc.
Keywords: cyclic carbonate; Dimethyl carbonate; double metal cyanide Fe-Zn complexes; organic carbonate; transesterification catalyst

Hydrophobic, solid acid catalysts for production of biofuels and lubricants - Sreeprasanth, Pulinthanathu Sree; Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Applied Catalysis A-General, 2006)
A novel application of Fe-Zn double-metal cyanide (DMC) complexes as solid catalysts in the preparation of fatty acid alkyl esters (biodiesel/biolubricants) from vegetable oils is reported. The catalysts are hydrophobic (no H2O adsorption at reaction temperatures) and contain only Lewis acidic sites (NH3 and pyridine adsorption). Bronsted acid sites are absent (absence of 1546 and 1639 cm(-1) bands on adsorption of pyridine). Basic sites are also absent (no CO2 adsorption). Unlike the homogeneous or other solid catalysts (like ZnO-Al2O3, for example), the Fe-Zn, DMC catalysts are highly active even for the simultaneous transesterification of triglycerides and esterification of the free fatty acids (FFA) present in unrefined and waste cooking oils as well as non-edible oils. They are also tolerant of water, probably, due to their surface hydrophobicity. A relationship between the transesterification activity and the concentration of strong Lewis acid sites has been observed. Coordinatively unsaturated Zn2+ ions in the structure of the Fe-Zn complex are the probable active sites. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alcoholysis of vegetable oils; Biodiesel; Biolubricants; double-metal cyanides (DMC); esterification of free fatty acids; fatty acid alkyl esters; fatty acid methyl esters; solid Fe-Zn catalysts; transesterification of vegetable oils

Sites for CO2 activation over amine-functionalized mesoporous Ti(Al)-SBA-15 catalysts - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Microporous and Mesoporous Materials, 2006)
{Activation of CO and its utilization in the synthesis of chloropropene and styrene carbonates over functionalized, mesoporous SBA-15 solids, have been investigated. The surface basicity of SBA-15 was modified with nitrogen-based organic molecules of varying basicity viz., alkyl amines (-NH2), adenine (Ade), imidazole (Im) and guanine (Gua). The surface of SBA-15 was also functionalized with Ti4+ and Al3+ species. The acid-base properties of these modified SBA-15 materials were investigated by temperature-programmed desorption (TPD) and diffuse-reflectance infrared Fourier transform (DRIFT) spectroscopy. NH3 and pyridine were used as probe molecules for acid sites, while CO, was used to characterize the basic sites. CO was activated at the basic amine sites forming surface carbamate species (IR peaks: 1609 and 1446 cm(-1)). The latter reacted further with epoxides adsorbed on the acid sites forming cyclic carbonates. A correlation between the intensity of the IR peak at 1609 cm(-1) and cyclic carbonate yield has been observed. The cyclic carbonate yields were higher when both the acid and base functionalities were present on the surface. The Ti- and Al-SBA-15 functionalized with adenine exhibited the highest catalytic activity and selectivity. There is an optimal dependence (''
Keywords: aromatization; Ga-based zeolites; propane; Si/Al ratio; Si/Ga ratio; zeolitic factors

Syntheses of polycarbonate and polyurethane precursors utilizing CO2 over highly efficient, solid as-synthesized MCM-41 catalyst - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Tetrahedron Letters, 2006)
As-synthesized MCM-41 was used as a reusable, heterogeneous catalyst for the eco-friendly synthesis of cyclic carbonate precursors of polycarbonates via a cycloaddition reaction of CO2 with epoxides. This catalyst is also efficient for the synthesis of alkyl and aryl carbamate precursors of polyurethanes via the reaction of amines, CO2 and alkyl halides. Both these reactions were carried out under mild conditions and without using any solvent or co-catalyst. CO2 is utilized as a raw material replacement for toxic phosgene in the conventional synthesis of these chemicals. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: carbamates; carbon dioxide utilization; CO2 fixation; cyclic carbonates; eco-friendly processes; MCM-41; polycarbonates; polyurethanes

Chemoselective alkane oxidations by reactive superoxovanadium(V) species in vanadosilicate molecular sieves - Srinivas, D.; Ratnasamy, P. (From ZEOLITES to Porous Mof Materials: The 40th Anniversary of International ZEOLITE Conference, Proceedings of The 15th International ZEOLITE Conference, 2007)
Unlike their titanium analogs, vanadosilicate molecular sieves catalyze the oxidation of the terminal (primary) C-H bonds in paraffins. This dissimilarity is attributed to differences in the type of reactive superoxo species generated on contact with oxidant. The latter were identified and characterized by in situ EPR and DRUV-vis spectroscopic techniques. By a suitable choice of silicate structure (VS-1 or V-MCM-41), solvent and oxidant (H(2)O(2), tert.-butyl hydroperoxide or H(2)+O2()), the V-O bond covalency and mode of O-O bond cleavage in the oxo-species and thereby, the chemoselectivity in the oxidation of the terminal carbon atoms in paraffins could be controlled.

Spectroscopic and catalytic properties of SBA-15 molecular sieves functionalized with acidic and basic moieties - Srinivas, D.; Ratnasamy, P. (Microporous and Mesoporous Materials, 2007)
SBA-15, grafted with Lewis acidic Ti4+ ions and basic amines (imidazole, guanine or adenine) exhibited high catalytic activity in the cycloaddition of CO2 to epoxides yielding selectively cyclic carbonate precursors of polycarbonates. In the second class of materials, the surface of SBA-15 was grafted with thiol or sulfonic acid functionalities. Mn(Salen)Cl was, then, covalently bound to these acidic groups. The resulting catalysts show enhanced chemo-, regio- and stereo-selective catalytic activity in the epoxidation of terpenes such as R-(+)limonene, alpha-pinene and Delta-carene with molecular oxygen. The acid-base properties of these modified SBA- 15 materials were investigated by temperature-programmed desorption and diffuse-reflectance infrared Fourier transform spectroscopy. Ammonia and pyridine were used as probe molecules for acidic sites and CO2 for basic sites. Acidic Ti sites activated epoxides and the grafted basic amines activated CO2. The simultaneous presence of both acidic and basic sites on amine/adenine-functionalized Ti-SBA-15 enabled synergistic enhancement in catalytic activity in the cycloaddition reaction of CO2 to epoxides. When Mn(Salen)Cl was immobilized on thiol or sulfonic acid-functionalized SBA-15, the oxidation state of Mn decreased from +3 to +2. The organo-acidic functional groups (thiol or sulfonic acid) axialk, coordinated to Mn ions modified the electronic structure of Mn ions enhancing the activity and selectivity of Mn(Salen) complexes in aerial oxidation reactions. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: aerial oxidation of terpenes; CO2 utilization; cyclic carbonates synthesis; epoxidation; functionalization with acidic and basic moieties; immobilization of Mn complexes; organo-functionalization of SBA-15; solid acid-base catalysts

Effect of fuel and its concentration on the nature of Mn in Mn/CeO2 solid solutions prepared by solution combustion synthesis - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, Veda (Acta Materialia, 2008)
Nano and microcrystalline, Mn/CeO2 solid solutions (5 mol.% Mn) have been prepared by solution combustion synthesis using urea, glycine or polyethylene glycol (PEG) as fuel. The nature of the fuel and its concentration (fuel to metal mole ratio, F/M have a strong influence on the physical and chemical characteristics of the resulting Mn/CeO2 solid solutions. The variations in the physicochemical properties are attributed to differences in (i) the adiabatic/real flame temperature realized with these fuels at different F/M ratios; (ii) the sustenance of the temperature or the quenching effect of the fuel at higher F/M ratios; (iii) combustion or decomposition of the precursors as the main course of the reaction; and (iv) the generation of gaseous products during combustion. Since the addition of the fuel to the initial precursor solution does not change the pH of the medium, the differences in the type of Mn species formed are mainly attributed to the combustion process. (C) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; Mn-ceria; Nanocomposites; X-ray diffraction (XRD); X-ray photoelectron spectroscopy (XPS)

EPR and DRS evidence for NO2 sensing in Al-doped ZnO - Navale, Shalaka C.; Ravi, V.; Srinivas, D.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2008)
Zinc oxide (ZnO) is a well-known semiconducting multifunctional material wherein properties right from the morphology to gas sensitivity can be tailor-made by doping or surface modification. Aluminum (Al)-incorporated porous zinc oxide (AI:ZnO) exhibits good response towards NO2 at low-operating temperature. The NO2 gas concentration as low as 20 ppm exhibits S = 17% for 5 wt. % Al-incorporated ZnO. The NO2 response increases with operating temperature and concentration and reaches to its maximum at 300 degrees C without any interference from other gases such as SO3, HCl, LPG and alcohol. Physico-chemical characterization likes differential thermogravimetric analysis (TG-DTA) electron paramagnetic resonance (EPR) and diffused reflectance spectroscopy (DRS) have been used to understand the sensing behavior for pure and A]-incorporated ZnO. The TG-DTA depicts formation of ZnO phase at 287 degrees C. The EPR study reveals distinct variation for O- (g=2.003) and Zn interstitial (g = 1.98) defect sites in pure and Al:ZnO. The DRS studies elucidate signature of adsorbed NO, species in aluminium-incorporated zinc oxide indicating its tendency to adsorb these species even at low temperatures. This paper is an attempt to correlate the gas sensing behavior with the physico-chemical studies such as EPR and DRS. (c) 2007 Published by Elsevier B.V.
Keywords: aluminum doping; DRS; EPR; NO2 sensor; ZnO

Vitamin K-3 family members - Part II: Single crystal X-ray structures, temperature-induced packing polymorphism, magneto-structural correlations and probable anti-oncogenic candidature - Rane, Sandhya; Ahmed, Khursheed; Salunke-Gawali, Sunita; Zaware, Santosh B.; Srinivas, D.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Temperature-induced packing polymorphism is observed for vitamin K-3 (menadione, 3-methyl-1,4-naphthoquinone, 1). Form la crystallizes at 300 K and 1b at 277 K both in the same space group P2(1)/c. Form 1b contains one molecule per asymmetric unit, performing anisotropy in g-factor viz. g(z) = 2.0082, g(y) = 2.0055 and g(x) = 2.0025, whereas form 1a contains two molecules in its asymmetric unit. Vitamin K-3 family members 2, [2-hydroxy vitamin K-3] and 3, [2-hydroxy-1-oximino vitamin K-3] also perform intrinsic neutral active naphthosemiquinone valence tautomers even in dark having spin concentrations due to hydrogen bonding and aromatic stacking interactions which are compared to vitamin K-3. The significant lateral C-H center dot center dot center dot O and O-H center dot center dot center dot pi bifurcated or pi-pi(center dot) interactions are discussed for molecular associations and radical formations. X-ray structure of 3 revealed pi-pi(center dot) stack dimers as radicals signatured in PR as triplet with five hyperfine splits [(A) over bar(N-14) = 11.9 G]. The centrosymmetric biradicals in 3 show diamagnetism at high temperature but below 10 K it shows paramagnetism with mu(eff) as 0.19 B.M. Vitamin K-3 and its family members inhibit biological activities of acid phosphatase (APase), which are proportional to their spin concentrations. This may relate to their probable anti-oncogenic candidature in future. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Anti-oncogenic candidature; H-bonding; Magneto-structural correlations; Naphthosemiquinones in vitamin K-3 family; Packing polymorphism; Spin concentrations

Estimation of free fatty acid content in oils, fats, and biodiesel by (1)H NMR spectroscopy - Satyarthi, Jitendra K.; Srinivas, D.; Ratnasamy, Paul (Energy & Fuels, 2009)
A novel (1)H NMR method for the quantification of free fatty acid (FFA) content in vegetable oils, animal fats, and biodiesel is reported. Nonedible oils and animal fats, which are increasingly being explored as cheaper, renewable feed stocks for biodiesel production by transesterification with methanol, contain a significant amount of FFA along with other acidic impurities. The (1)H NMR spectroscopic method is found to be more accurate than the conventional titrimetric analysis for the estimation of FFA content especially in those cases where acidic entities other than the FFA are also present in the feedstock. The titrimetric methods provide a gross acid value which corresponds to that of FFA and other acidic impurities. Our NMR method provides the FFA content exclusively. In the case of refined edible oils (wherein the other acidic impurities are negligible), the results obtained from the (1)H NMR method are comparable with those from the titrimetic analysis.

Redox and selective oxidation properties of Mn complexes grafted on SBA-15 - Saikia, Lakshi; Srinivas, D. (Catalysis Today, 2009)
Manganese complexes of 5,10,15,20-tetraphenylporphyrin (Mn(TPP)Cl) were grafted on SBA-15 functionalized with propyl-amine, -thiol and -sulfonic acid groups. The acido-basic properties of the support influenced the oxidation state, redox behavior and selective oxidation properties of the Mn complexes. Acidic supports (SBA-15-pr-SH and SBA-15-pr-SO(3)H) promoted the reduction of Mn ions in Mn-TPP complexes from 3+ to 2+ oxidation state. A similar behavior was found also when Mn(Salen)Cl complexes were immobilized on those supports. However, the extent of such facile reduction was more in the case of Mn-TPP than in Mn-Salen complexes. The former exhibited superior catalytic activity (turnover frequency) than the latter-type Mn complexes in regio-, stereo- and chemoselective oxidation of R-(+)-limonene with molecular oxygen (1 atm) at ambient temperatures. The catalytic oxidation activity correlates with the redox behavior of the grafted Mn complexes. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Grafted manganese complexes; Mn(Salen)Cl; Mn(TPP)Cl; Organo-functionalized SBA-15; Redox behavior of Mn; Selective oxidation of limonene

Selective oxidation of benzyl alcohol over copper phthalocyanine immobilized on MCM-41 - Hamza, A.; Srinivas, D. (Catalysis Letters, 2009)
Copper phthalocyanine (CuPc) complexes immobilized on ``neat'' and Ti(4+) and Al(3+) containing MCM-41 mimic the functionality of metalloenzymes. These novel materials catalyze the oxidation of benzyl alcohol to selectively benzaldehyde at moderate temperatures using peroxides and molecular oxygen as oxidant. Electron paramagnetic resonance and X-ray photoelectron spectroscopic studies revealed that the acidity of the support (MCM-41) influences the electronic structure of the immobilized CuPc. On acidic supports a part of copper in CuPc got reduced from a ``formal'' +2 to +1 oxidation state. This reduction of copper in its oxidation state on different supports decreased in the order: Al-MCM-41 (Bronsted and strong Lewis acid sites) > MCM-41 (silanol sites) > Ti-MCM-41 (weak Lewis acid sites). A linear variation in catalytic activity with the concentration of Cu(1+) ions in different catalyst samples was observed. The study reveals that by suitably modifying the acidic properties of the support one can, in principle, fine-tune the electronic and catalytic properties of the active oxidation sites.
Keywords: Copper phthalocyanine; EPR; MCM-41; Selective oxidation of benzyl alcohol; UV-visible spectroscopy

Chemoselective hydrogenation of cinnamaldehyde over Pd/CeO2-ZrO2 catalysts - Bhogeswararao, Seemala; Srinivas, D. (Catalysis Letters, 2010)
Selective hydrogenation of cinnamaldehyde over Pd (2 wt%) supported on CeO2, ZrO2 and CeO2-ZrO2 catalysts is reported for the first time. In general, the olefinic (C=C) group of cinnamaldehyde is preferentially hydrogenated compared to the carbonyl (C=O) group. This selectivity preference could, however, be altered or reversed by adding alkali additives to the catalyst. The influence of additive on the structure and redox properties of the active sites and correlation of that with selective hydrogenation activity is investigated.
Keywords: alpha; beta-Unsaturated aldehyde; Ceria-zirconia; Cinnamaldehyde; Hydrogenation; palladium catalyst

Esterification of fatty acids with glycerol over Fe-Zn double-metal cyanide catalyst - Kotwal, Mehejabeen; Deshpande, Suvarna S.; Srinivas, D. (Catalysis Communications, 2011)
Solid Fe-Zn double-metal cyanide (DMC) complex exhibits high catalytic activity for esterification of fatty acids (FA) with glycerol. DMC catalysts with varying acidities were prepared by synthesizing the material at four different temperatures (10, 25, 50 and 80 degrees C). The catalyst prepared at 50 degrees C exhibited highest catalytic activity. Catalytic activity of DMC was influenced by both acidity and surface area. Complete conversion of FA was achieved at 140-200 degrees C under atmospheric pressure. Chain length of FA was found to influence the rate of reaction and product selectivity. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Acid-catalyzed reaction; Double-metal cyanide (DMC); Esterification of fatty acid; Fatty acid glycerides; solid acid catalyst

Hydrolysis of vegetable oils and fats to fatty acids over solid acid catalysts - Satyarthi, J. K.; Srinivas, D.; Ratnasamy, P. (Applied Catalysis A-General, 2011)
Solid Fe-Zn double-metal cyanide (DMC) complexes exhibit high catalytic activity for hydrolysis of edible and non-edible vegetable oils and animal fat. In a batch reaction, complete conversion of vegetable oil triglycerides to fatty acids with selectivity greater than 73 wt% was obtained at temperatures as low as 463 K, autogenous pressure and with 5 wt% of catalyst. Catalytic activity of DMC was superior to Amberlyst (TM) 70, SAPO-11, H-beta, HY, MoO(x)/Al(2)O(3) and sulfated zirconia. Rates of hydrolysis were greatly enhanced when solvents (tetrahydrofuran or N,N-dimethylformamide), phase transfer agents (tetrapropyl ammonium bromide) and products (a mixture of mono-/diglycerides and fatty acids) or fatty acid was added to the feed. Surface hydrophobicity which enables high wettability and activation of glycerides on active, acidic sites of reusable DMC is attributed to be the major cause for its superior catalytic activity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Double-metal cyanide complex; Fat splitting; Fatty acids; Hydrolysis of vegetable oils and fats; solid acid catalyst

Lanthanum and zinc incorporated hydrotalcites as solid base catalysts for biodiesel and biolubricants production - Rahul, R.; Satyarthi, Jitendra K.; Srinivas, D. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2011)
Mg-Al hydrotalcites doped with varying amounts of lanthanum and zinc ions (10 30 mol %) have been prepared by co-precipitation method and used, after calcination at 873 K, as solid base catalysts for transesterification of soybean oil with methanol (producing biodiesel) and n-octanol (producing biolubricants). The catalyst with 20 mol % of lanthanum shows the highest transesterification activity (soybean oil conversion = 100 % and biodiesel yield = 95 %) at 423 K in 4 h. Catalytic activity varies in proportion with the basicity of the catalysts.
Keywords: Biodiesel; Biolubricants; catalysis; Doped hydrotalcites; Hydrotalcites; Lanthanum; Solid base catalysts; transesterification; Vegetable oils; zinc

Selective epoxidation of methyl soyate over alumina-supported group VI metal oxide catalysts - Satyarthi, Jitendra K.; Srinivas, D. (Applied Catalysis A-General, 2011)
Epoxidation of methyl soyate (biodiesel), soybean oil and oleic acid with tert.-butyl hydroperoxide (TBHP) was investigated over gamma-alumina-supported group VI metal oxides (CrOx/Al2O3, MoOx/Al2O3 and WOx/Al2O3) prepared by impregnation method. The studies revealed that 15 wt% MoOx on gamma-Al2O3 was the most active catalyst (conversion >90 mol% under optimized conditions). While MoOx/Al2O3 is selective mainly for epoxidation, the other catalysts are active for epoxidation as well as for decomposition of TBHP. The active species on the catalyst surface were investigated using in situ UV-visible spectroscopy. A linear correlation was observed between epoxidation activity and surface acidity of the catalyst. A new H-1 NMR method was developed to monitor the progress of epoxidation reaction which was found to be superior to gas chromatographic method in estimating the conversion of double bonds of fatty compounds. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Alumina-supported group VI metal oxides; Biodiesel; epoxidation; Fatty acids; H-1 NMR spectroscopy; MoOx/Al2O3; Vegetable oil

Calcined, rare earth modified hydrotalcite as a solid, reusable catalyst for dimethyl carbonate synthesis - Unnikrishnan, P.; Srinivas, D. (Industrial & Engineering Chemistry Research, 2012)
An eco-friendly building block and fuel additive dimethyl-carbonate (DMC)-was synthesized through a benign route by transesterification of propylene carbonate (PC) with methanol. The catalytic activity of a series of calcined, rare earth elements (La3+, Ce3+, Pr3+, Sm3+, and Y3+; 2-10 mol %) incorporated Mg-Al hydrotalcites (HT) was evaluated for this reaction. Among several, the La (8 mol %) modified HT showed the highest activity (PC conversion = 65.4 mol % and DMC selectivity = 88 mol % at 150 degrees C and in 2 h). Basicity of the catalyst played an important role on the transesterification activity. The influence of reaction parameters and calcination temperature on the catalytic activity of HT was investigated. The La modified HT catalyst was heterogeneous and could be reused with little loss of activity.

Intramolecular selective hydrogenation of cinnamaldehyde over CeO2-ZrO2-supported Pt catalysts - Bhogeswararao, Seemala; Srinivas, D. (Journal of Catalysis, 2012)
Selective liquid phase hydrogenation of cinnamaldehyde is reported, for the first time, over CeO2, ZrO2, and CeO2-ZrO2-supported Pt catalysts. Cinnamyl alcohol is the selective product. These catalysts are highly active and selective even at 25 degrees C and found to be superior to most of the hitherto known supported Pt catalysts. Alkali addition (NaOH) has enhanced the performance of these catalysts. At an optimized reaction condition, 95.8% conversion of cinnamaldehyde and 93.4% selectivity of cinnamyl alcohol have been obtained. Acidity of the support (due to the presence of ZrO2 component) and higher electron density at Pt (due to CeO2 component) are attributed to be responsible for the superior catalytic activity of Pt supported on CeO2-ZrO2 composite material. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: alpha; beta-Unsaturated aldehyde; Ceria-zirconia; Cinnamaldehyde; Hydrogenation; Promotion by alkali ions; Supported Pt catalyst

Noble metal promoted CeO2-ZrO2-supported ni catalysts for liquid-phase hydrogenation of cinnamaldehyde - Bhogeswararao, Seemala; Kumar, V. Pavan; Chary, K. V. R.; Srinivas, D. (Catalysis Letters, 2013)
Pd or Pt promoted CeO2-ZrO2-supported Ni catalysts exhibited superior catalytic activity to the hitherto known Ni catalysts for liquid-phase hydrogenation of cinnamaldehyde at moderate conditions. Under similar experimental conditions, the unpromoted catalyst was selective for hydrocinnamaldehyde product (C=C hydrogenation) whereas the promoted catalyst yielded 3-phenyl propanol (C=C and C=O hydrogenation product). Enhanced dispersion of Ni was the cause for higher activity of the promoted Ni catalysts.
Keywords: Ceria-zirconia; Cinnamaldehyde; Noble metal promoted catalyst; Selective hydrogenation; Supported Ni catalyst

Zirconium phenyl phosphonate phosphite as a highly active, reusable, solid acid catalyst for producing fatty acid polyol esters - Varhadi, Poonam; Kotwal, Mehejabeen; Srinivas, D. (Applied Catalysis A-General, 2013)
The application of zirconium phenyl phosphonate phosphite (ZrPP) as a solid acid catalyst for producing polyol esters by esterification of glycerol or trimethylolpropane with a fatty acid (C-8-C-18.1) is reported for the first time. ZrPP exhibits high catalytic activity and in particular, (di + tri) esters selectivity (92.3 mol%). These esters of polyols are known for their application as biolubricants. The catalyst prepared using phosphorous acid to phenyl phosphonic acid molar ratio of 3:1 was found superior. The influence of process parameters on activity and selectivity of the catalyst was investigated. ZrPP was reusable in at least three recycling experiments. Hydrophobicity due to exposed phenyl groups on the surface is the possible cause for superior esterification activity of this novel, solid catalyst. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biolubricants; Esterification of fatty acid; Fatty acid glycerides; Hydrophobic solid acid catalyst; Polyol esters; Zirconium phenyl phosphonate phosphite

Catalytic conversion of furfural to industrial chemicals over supported Pt and Pd catalysts - Bhogeswararao, Seemala; Srinivas, D. (Journal of Catalysis, 2015)
Several industrial chemicals were prepared by hydrogenation of furfural over gamma-Al2O3-supported Pt and Pd catalysts. These catalysts were active even at room temperature (25 degrees C). While the Pt catalysts were selective for C=O hydrogenation (yielding furfuryl alcohol), Pd facilitated ring hydrogenation (producing tetrahydrofurfuryl alcohol). At high temperature (240 degrees C), the Pd catalyst exhibited excellent decarbonylation activity forming furan with 85% yield. The catalyst was reusable even in the absence of external hydrogen. The presence of hydrogen led to ring-opened products. Furan was quantitatively converted at 25 degrees C to tetrahydrofuran. Acidity of the support made a marked influence on the activity and selectivity. Pt on SO4-ZrO2 favored hydrogenolysis yielding 2-methyl furan along with furan with >75 wt% selectivity. Particle size, metal dispersion, and solvent influenced catalytic activity. Differences in structure and mode of furfural adsorption were also the causes for variations in selectivity of these supported Pt and Pd catalysts. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Biomass to fuels and chemicals; Decarbonylation; furfural; Hydrogenation; Hydrogenolysis; Supported Pt and Pd catalysts

Highly active and reusable ternary oxide catalyst for dialkyl carbonates synthesis - Unnikrishnan, P.; Srinivas, D. (Journal of Molecular Catalysis A-Chemical, 2015)
The application of ternary oxides, prepared through calcination of rare-earth modified Mg/Al-hydrotalcite (HT), as highly active, selective, and reusable solid catalysts for dialkyl carbonates synthesis by transesterification reaction is reported. Dimethyl carbonate, for example, was prepared by reacting ethylene carbonate with methanol in 100 mol% selectivity at a yield of 95 mol%. Among several rare-earth modified precursors, La (10 mol%)-HT showed the highest activity. This catalyst was active even at ambient conditions. Basicity of the catalyst played crucial role on its performance. The activity of these catalysts was superior to the hitherto known solid catalysts for this reaction. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Dialkyl carbonate; Dimethyl carbonate (DMC); Rare-earth modified hydrotalcite; Solid base catalyst; Ternary oxide; Transesterification of cyclic carbonate

Heterogeneous catalysis - Unnikrishnan, P.; Srinivas, D. (Industrial catalytic processes for fine and specialty chemicals, 2016)
A majority of industrial catalytic processes use heterogeneous catalysts because of their engineering advantages. At present, heterogeneous catalysis covers almost 80% of the global market share. The demand for heterogeneous catalysis is growing annually. In 2010, it was about US 14 billion and expected estimation of it in 2015 is around 20 billion. Understanding at the molecular level the way surfaces of solids catalyze chemical reactions is a challenge in this area of research. This chapter introduces the fundamentals of heterogeneous catalysis, current industrial practices using solid catalysts, reaction steps involved in heterogeneous catalysis, conventional and advanced methods of catalyst preparation, catalyst characterization techniques, causes for catalyst deactivation, steps to avoid deactivation, and methods of catalyst reactivation.